2021
DOI: 10.1007/s10592-021-01421-7
|View full text |Cite
|
Sign up to set email alerts
|

Population genetic structure of the Natterjack toad (Epidalea calamita) in Ireland: implications for conservation management

Abstract: Molecular methods can play a crucial role in species management and conservation. Despite the usefulness of genetic approaches, they are often not explicitly included as part of species recovery plans and conservation practises. The Natterjack toad (Epidalea calamita) is regionally Red-Listed as Endangered in Ireland. The species is declining and is now present at just seven sites within a highly restricted range. This study used 13 highly polymorphic microsatellite markers to analyse the population genetic di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 100 publications
(104 reference statements)
0
10
0
Order By: Relevance
“…Other demographic parameters such as low local breeding success may also contribute to lower recruitment and dispersal. Certainly, Natterjack toadsat Killeen and Roscullen have exhibited substantial census size declines over the past 15 years (Reyne et al 2019(Reyne et al , 2021b. We propose including Killeen and Roscullen in the Natterjack toad NPWS 'Head-start and Reintroduction Programme' with occupied breeding sites used as a source population, with assisted migration and translocation to adjacent artificial ponds.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Other demographic parameters such as low local breeding success may also contribute to lower recruitment and dispersal. Certainly, Natterjack toadsat Killeen and Roscullen have exhibited substantial census size declines over the past 15 years (Reyne et al 2019(Reyne et al , 2021b. We propose including Killeen and Roscullen in the Natterjack toad NPWS 'Head-start and Reintroduction Programme' with occupied breeding sites used as a source population, with assisted migration and translocation to adjacent artificial ponds.…”
Section: Discussionmentioning
confidence: 99%
“…The main habitats in this area are sand dunes and grasslands both identified in the present study as facilitating dispersal and gene flow. Cox et al (2017) demonstrated that dispersal of the Natterjack toad is facilitated by sand dunes and beaches, and the largest Natterjack toad population in Ireland is in the Magharees sand dune system, but breeding depends on the formation of ephemeral breeding pools in sand dune slacks (Reyne et al 2019(Reyne et al , 2021b. Access to permanent ponds at the nearby Castlegregory Golf Course (CGC) and suitable sites along the lakeshore of Lough Gill provide a valuable alternative in dry years, thus maintaining connectivity between the breeding sites is essential.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations